(untitled) (Research, Society and Development, 2021)
Objective: To analyze the characteristics of sexual behavior of adolescents from public and private schools in the city of Porto Alegre, according to PENSE conducted in 2015. Method: This is a descriptive, cross-sectional study, with a quantitative approach, which used secondary data of a national survey of 9th grade elementary school students from public and private schools in the city of Porto Alegre who participated in PeNSE, held in 2015. Results: Of the 1011 participants, 465 are male (54.0%) ; 40.6% (n = 410) stated that they had had sexual intercourse and the majority reported having started sexual life at the age of 14 (151; 37.2%). As for sexual behavior, boys reported beginning their sexual life earlier, when compared to girls, and reported not knowing whether or not they used any method to prevent pregnancy. Conclusions: It is concluded that primary care health professionals should pay special attention to male adolescents, as they have early sexual initiation and a greater number of partners.